Ontstaan en eerste periode van die Hervormde teologiese opleiding aan die Universiteit van Pretoria - Loader, James Alfred (Hervormde teologiese studies, 1989)
Establishment and first period of the Hervormde theological training at the University of Pretoria In this study the establishment of the Hervormde theological training at the University of Pretoria is researched with the purpose of identifying the ecclesiastical, religious and theological factors that influenced the emergence and development of a typical Hervormde type of theology in South Africa. It is argued that the resistance of the Transvaal Afrikaners to religious encroachment of th e ir independence in the Boer Republic of the nineteenth century caused distrust of the church and theology associated with Stellenbosch in the British Cape Colony, and that opposition to trends from there determined the association of the Transvaal Hervormers with certain Dutch circles. From the joining of these two forces - what the Transvaal Hervormers required and what the contemporary Dutch theologies could offer - sprang the roots of what Hervormde theology came to be.